2012
DOI: 10.1136/medethics-2011-100055
|View full text |Cite
|
Sign up to set email alerts
|

Predictive genetic testing in minors for late-onset conditions: a chronological and analytical review of the ethical arguments: Figure 1

Abstract: Predictive genetic testing is now routinely offered to asymptomatic adults at risk for genetic disease. However, testing of minors at risk for adult-onset conditions, where no treatment or preventive intervention exists, has evoked greater controversy and inspired a debate spanning two decades. This review aims to provide a detailed longitudinal analysis and concludes by examining the debate's current status and prospects for the future. Fifty-three relevant theoretical papers published between 1990 and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 53 publications
(226 reference statements)
2
64
0
Order By: Relevance
“…8 Competence can be described as task or domain specific. 38 An individual may be competent to make one medical decision without being competent to make another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Competence can be described as task or domain specific. 38 An individual may be competent to make one medical decision without being competent to make another.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 More than two decades since the publication of the first guidelines, considerable disagreement between commentators remains. 8 The ethical debate concerning predictive genetic testing in young people has become mired in a conflicting set of opinions, assumptions, and speculation, with little relevant evidence to inform these. 9 Two overarching concerns dominate the arguments against predictive genetic testing in young people: (i) young people lack the competence to comprehend the significance of a predictive genetic test and may regret their decision later in life, and (ii) young people who receive a gene-positive test result (the presence of the relevant family mutation) are at risk of adverse psychosocial consequences.…”
mentioning
confidence: 99%
“…Arguments against testing focused on potential harms including decreasing self-esteem, increasing anxiety, and limiting future choices [Malpas, 2006;Mand et al, 2012]. As this test was used in clinical practice, the predictions of severe negative psychological consequences were not fulfilled [Duncan and Delatycki, 2006;Wade et al, 2010], and arguments regarding potential psychological and social benefits developed, for example, decreasing anxiety, and facilitating family and career planning [Malpas, 2008;Mand et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines apply to genomic findings in children and adults and therefore deviate from earlier professional guidelines against testing for adult-onset disorders in minors (Borry et al 2006;ESHG 2009). Whether testing for adult-onset disorders in children, and by deduction prenatally, should be limited is a matter of debate on its own (Mand et al 2012;Anderson et al 2014), but existing guidelines were directed toward actively seeking testing for adult-onset conditions and predated the era of genome-wide sequencing with its potential to uncover such findings incidentally and unintentionally. Recent survey studies have indicated that probands and parents of children undergoing WES are interested in having incidental findings disclosed (Townsend et al 2012;Fernandez et al 2014;Shahmirzadi et al 2014).…”
Section: Management Of Incidental Findingsmentioning
confidence: 99%